Is thromboprophylaxis effective in reducing the pulmonary thromboembolism? - Rajabi, Fereshteh (Isfahan Cardiovascular Research Center, Isfahan University of Medical Sciences, 2012)
BACKGROUND: Deep vein thrombosis (DVT) is a relatively prevalent disease which causes high costs due to the required diagnostic tests, specialized treatments, and hospital admission. In recent decades, implementation of thromboprophylaxis protocols has significantly reduced the incidence of thromboembolism in hospitals. The present study aimed to compare the incidence of venous thromboembolism before and after implementation of the mentioned protocol in hospital with identified risk factors and underlying diseases. METHODS: In this case-control group, 385 patients at the risk of DVT, some before and some after implementation of the protocol were studied. Therefore, the level of thromboprophylaxis and the incidence of venous thromboembolism were compared before and after the protocol. Data was entered into SPSS(15) and analyzed by chi-square and t tests RESULTS: Out of 385 patients, 34 patients (8.8%) had venous thromboembolism while 351 (91.2%) were not affected. The incidence of venous thromboembolism was significantly different before and after the implementation of the protocol (17.7% vs. 5.9%; P < 0.001). The incidence of venous thromboembolism in patients not receiving thromboprophylaxis was almost 5 times higher than those who received it (20.7% vs. 5.1%). The frequency distribution of thromboembolism had a significant difference in the two above mentioned groups (P < 0.001). CONCLUSION: Thromboprophylaxis protocol reduced venous thromboembolism incidence in patients with underlying diseases which increase the risk of the complication.